Pharmacogenetics in Pancreatic Cancer - Tourkantonis, Ioannis S; Peponi, Evangelia; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2014)
Pancreatic cancer is an aggressive malignancy with a poor overall survival rate. Given advances in pharmacogenomics, numerous gene mutations have been identified that could be potential targets for drug development. Therefore, future research strategies may identify prognostic and predictive markers aiming to improve outcome by maximizing efficacy whilst lowering toxicity. In this commentary, we summarize several interesting results regarding pancreatic cancer pharmacogenetics that have been presented in the 2014 American Society of Clinical Oncology (ASCO) Annual Meeting. In particular, we focus on Abstract #4124, which investigated the potential predictive role of human equilibrative nucleoside transporter 1 (hENT1) in patients treated with adjuvant gemcitabine for pancreatic cancer, on Abstract #4125, which examined the tolerability of a modified FOLFORINOX study based on UGT1A1*28 genotype guided dosing of IRI in patients with advanced pancreatic cancer, and on Abstract #4130, which confirmed the predictive role of circulating tumor and invasive cells (CTICs) from patients with unresectable pancreatic cancer in second-line chemotherapy treatment setting. Image: Cellular metabolism of gemcitabine.